2011
DOI: 10.1002/med.20182
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibitors: Scope of their use and development in cancer chemotherapy

Abstract: The traditional nonsteroidal anti-inflammatory drugs (NSAIDs) exert their effect by inhibition of cyclooxygenase-1 (COX-1) as well as COX-2 enzymes. As COX-1 is responsible for maintaining normal biological functions, the nonselective inhibition of these enzymes caused side effects including gastrointestinal (GI) problems. Recently developed selective COX-2 inhibitors could reduce these adverse effects, but the evidence of cardiovascular side effects including an increased risk of myocardial infarction began t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 168 publications
(157 reference statements)
0
39
0
Order By: Relevance
“…Although the benefit of aspirin for patients with cancer has been widely appreciated, the mechanism behind remains largely unclear. Previous understandings tend to attribute the anticancer potential of aspirin to the inhibition of cyclooxygenase-2 (COX-2), which is upregulated in various cancer cells (10,11). Of note, increasing evidence has suggested that aspirin may exhibit anticancer effects in a COX-independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Although the benefit of aspirin for patients with cancer has been widely appreciated, the mechanism behind remains largely unclear. Previous understandings tend to attribute the anticancer potential of aspirin to the inhibition of cyclooxygenase-2 (COX-2), which is upregulated in various cancer cells (10,11). Of note, increasing evidence has suggested that aspirin may exhibit anticancer effects in a COX-independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipase A2 (PLA 2 ) enzymes cleave membrane bound arachidonate for the conversion into bioactive precursors. AA can be metabolized through COX pathway via a two-step process: the first step involves conversion of AA to prostaglandin G2 (PGG 2 ), a 9,11-endoperoxide-15-hydroperoxide, and in the second step peroxidase reduces PGG 2 to prostaglandin H 2 (PGH 2 ). Specific PG synthases further metabolize PGH 2 to give structurally related bioactive lipids, including PGs PGE 2 , PGD 2 , PGF 2a , prostacycline PGI 2 and thromboxane A 2 (TxA2) [2].…”
Section: Introductionmentioning
confidence: 99%
“…PGE 2 specifically exerts carcinogenic effects in the human body. It was found that premalignant lesions and established cancers produce excessive quantities of PGE 2 and this enhances tumor cell growth and increases tumor invasiveness [1]. COX-2 is up-regulated in a number of epithelial cancers, including those originating in the colon and rectum, stomach, breast, prostate, and lung [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that cyclooxygenase enzymes may have a key role in carcinogenesis, thus inhibitors have the potential for cancer prevention (Axelsson et al, 2010;Flossmann et al, 2007;Khan & Lee, 2011). Recent studies suggest an important role of COX-2 inhibitors in bladder cancer therapy.…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%